Air-assisted devices reduce biomechanical loading in the low back and upper extremities during patient turning tasks. (September 2020) - Hwang, Jaejin; Ari, Hemateja; Matoo, Megha; Chen, Jie; Kim, Jeong Ho
Abstract: This laboratory study evaluated different assistive devices for reducing biomechanical loading during patient turning tasks. Twenty caregivers (18 females and 2 males) performed standardized patient turning tasks with two simulated patients (body mass: 74 kg and 102 kg). The turning tasks were performed in two turning directions (toward vs. away relative to caregivers) using five device conditions: draw sheet, friction-reducing turning sheet, air-assisted transfer device, air-assisted turning device, and no assistive device. Low back and upper extremity muscle activity, trunk and shoulder postures, low back moment, and self-reported usability ratings were evaluated. While all assistive devices reduced trunk flexion, both air-assisted transfer and turning devices reduced the trunk flexion ( p 's < 0.001) and muscle activity ( p 's < 0.001) in the erector spinae and triceps compared to no assistive device condition. These results suggest that the air-assisted devices have potential as an effective intervention to considerably reduce physical risk factors associated with caregivers' musculoskeletal disorders in low back and upper extremities. Highlights: Effects of patient turning devices on biomechanical stresses were evaluated. Air-assisted devices were effective to reduce stresses of low back and shoulders. Turning toward task showed lower stresses of the shoulders than turning away task.